2021
DOI: 10.3390/nu13041368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum CJLP55 on Clinical Improvement, Skin Condition and Urine Bacterial Extracellular Vesicles in Patients with Acne Vulgaris: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Lactobacillus plantarum CJLP55 has anti-pathogenic bacterial and anti-inflammatory activities in vitro. We investigated the dietary effect of CJLP55 supplement in patients with acne vulgaris, a prevalent inflammatory skin condition. Subjects ingested CJLP55 or placebo (n = 14 per group) supplements for 12 weeks in this double-blind, placebo-controlled randomized study. Acne lesion count and grade, skin sebum, hydration, pH and surface lipids were assessed. Metagenomic DNA analysis was performed on urine extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
1
23
0
2
Order By: Relevance
“…In recent times, the field of probiotics has extended the utilization of microbes to confer health benefits beyond the gastrointestinal tract. An example of this is evidence of improved vaginal and skin health with the application of Lactobacillus plantarum [ 8 , 21 , 35 ] . With this advancement, a new definition of the term was established by a panel of experts convened by the International Scientific Association for Probiotics and Prebiotics (ISAPP) [14] : “A substrate that is selectively utilized by host microorganisms conferring a health benefit”.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the field of probiotics has extended the utilization of microbes to confer health benefits beyond the gastrointestinal tract. An example of this is evidence of improved vaginal and skin health with the application of Lactobacillus plantarum [ 8 , 21 , 35 ] . With this advancement, a new definition of the term was established by a panel of experts convened by the International Scientific Association for Probiotics and Prebiotics (ISAPP) [14] : “A substrate that is selectively utilized by host microorganisms conferring a health benefit”.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was demonstrated that acne patients harbored diminished diversity and increased Bacteroidetes : Firmicutes ratio in the gut [ 54 ]. It was suggested that the intestinal bacterial dysbiosis found in patients with acne would enhance intestinal permeability, leading to the release of microbial molecules into the circulation that promote inflammation contributing to acne development [ 55 , 56 ]. Thus, the use of oral probiotic interventions for the treatment of acne has gained significant attention over the past decade [ 1 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study revealed that patients receiving oral Lacticaseibacillus rhamnosus SP1 for 12 weeks exhibited significant improvement of their acne lesions compared with the placebo control group [ 58 ]. More recently, the double-blind, placebo-controlled randomized study performed by Kim et al [ 56 ] demonstrated that the oral administration of Lactiplantibacillus plantarum CJLP55 to patients with acne during 12 weeks improved acne lesion count and grade, decreased sebum triglycerides, and increased skin hydration. Those beneficial effects were associated with an improvement in intestinal bacterial dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it may be hypothesized that topical probiotics could restore a more balanced microflora to decrease acne lesions. Investigated probiotics include L. plantarum , S. epidermidis , and other health-promoting bacterial strains; a reduction in lesion concentration, erythema, and pathogenic bacteria load with an improvement in the skin barrier function were reported [ 229 , 230 , 231 ]. One cutting-edge therapy is based on bacteriophages, or viruses that infect bacteria.…”
Section: Topical and Oral Probiotics In Skin Health And Diseases: State Of The Artmentioning
confidence: 99%